Physicochemical properties of the complex oxides in Sm-Ba-Me-Cu-O (Me = Fe, Co) systems - N. E. Volkova; K. M. Deryabina; L. Ya. Gavrilova; V. A. Cherepanov (Chimica Techno Acta)
The present work was focused on the studies of crystal structure, oxygen nonstoichiometry, thermal expansion of SmBaCo2−xCuxO6-δ and SmBaFe2−xCuxO6-δ. Values of the oxygen content in complex oxides SmBaCo2‑xCuxО6‑δ were determined over a wide temperature range in air using high temperature thermogravimetry and iodometric titration. Also, chemical stability with respect to Ce0.8Sm0.2O1.9 and Zr0.85Y0.15O1.93 two common solid electrolyte materials used for SOFCs was evaluated.